Salivary alpha-amylase activity and its association with early childhood caries and rampant caries experience: a cross-sectional study - Padmanabhan, Vivek; Islam, Md Sofiqul; Rahman, Muhammed Mustahsen; Goud, Manjunatha B. K.; Alshehhi, Latifa Majed Sulaiman Allay; Hamed, Hebah Mushref Ahmad; Haridas, Sheela; Sharma, Dileep (Frontiers in Medicine, 2025)
AimsThis study aims to evaluate salivary alpha-amylase levels in children diagnosed with Early Childhood Caries (ECC) and Rampant Caries (RC) and compare them to levels in children without ECC or RC. It also examines the relationship between salivary alpha-amylase levels and increased caries activity in the children with ECC or RC.Materials and methodsA cross-sectional study was conducted at RAK College of Dental Sciences (RAKCODS) with 100 children aged 3–12 years. Participants were divided into ECC and RC groups, each consisting of study and control groups. Salivary alpha-amylase levels were measured using Enzyme-Linked Immunosorbent Assay (ELISA) kits. Statistical analyses, including the Wilcoxon Signed Rank test and Pearson’s correlation coefficient, were performed using SPSS version 29 to compare salivary alpha-amylase levels between groups and examine correlation with severity of dental caries.ResultsThe study found that children with ECC and RC had significantly higher mean salivary alpha-amylase levels (16.046 U/mL and 20.62 U/mL, respectively) compared to control groups (5.09 U/mL and 12.70 U/mL). The differences were statistically significant (p < 0.0001). Pearson’s correlation coefficients indicated a strong positive correlation between salivary alpha-amylase levels and severity of dental caries in both ECC (r = 0.9891, p < 0.0001) and RC (r = 0.9142, p < 0.0001) groups.ConclusionThe study concludes that elevated salivary alpha-amylase levels, which are statistically significant, are observed in children with ECC and RC. Additionally, it was found that salivary alpha-amylase levels increased with the number of carious lesions. These findings suggest that salivary alpha-amylase could serve as a valuable biomarker for assessing caries risk and guiding preventive strategies.